2017
DOI: 10.1002/ejhf.743
|View full text |Cite
|
Sign up to set email alerts
|

Patient outcome after implant of a cardioverter defibrillator in the ‘real world’: the key role of co‐morbidities

Abstract: This article refers to 'The impact of co-morbidity burden on appropriate implantable cardioverter defibrillator therapy and all-cause mortality: insight from Danish nationwide clinical registers,' by A.C. Ruwald et al., published in this issue on pages 377-386.The use of implantable cardioverter defibrillators (ICDs) has significantly evolved in the last decades, following the pioneering experiences of Mirowski ∼35 years ago and related to very selected patients with a history of multiple cardiac arrests. 1 In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…102 Neutral results may be caused by both the type of the intervention and patients selection. For instance, in a recent randomized controlled trial, remote monitoring through the CRTdefibrillator, compared with standard therapy, did not reduce mortality or hospitalizations, primary endpoint of the study, with, however, a reduction in in-office visits.…”
Section: Telemedicinementioning
confidence: 99%
See 2 more Smart Citations
“…102 Neutral results may be caused by both the type of the intervention and patients selection. For instance, in a recent randomized controlled trial, remote monitoring through the CRTdefibrillator, compared with standard therapy, did not reduce mortality or hospitalizations, primary endpoint of the study, with, however, a reduction in in-office visits.…”
Section: Telemedicinementioning
confidence: 99%
“…101,102,188,189 The contribution of comorbidities to patients' outcomes may be similar in patients with HFrEF, compared with those with HFpEF, 189 or be larger in those with HFpEF according to other analyses. 101,102,188,189 The contribution of comorbidities to patients' outcomes may be similar in patients with HFrEF, compared with those with HFpEF, 189 or be larger in those with HFpEF according to other analyses.…”
Section: Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…clearly show that patients who are candidates for upgrade to CRT have a different profile as compared to de novo CRT implant: they are older, with higher prevalence of coronary artery disease, valvular heart disease, chronic kidney disease, anaemia, and atrial fibrillation. Most of these factors have been found to be associated with a worse response to CRT and a worse outcome, leading to an important clinical question: ‘What is the long‐term outcome of these patients?’. Upgrade to CRT has never been the subject of a randomized clinical study but a recent systematic review and meta‐analysis identified a total of 16 reports including 489 568 CRT recipients, of whom 21 363 patients underwent an upgrade procedure.…”
mentioning
confidence: 99%
“…The upgrade from a PM to a CRT-D is technically complex, and at least in non-ischaemic cardiomyopathy should occur less frequently in the future considering the mean age of patients with a previous implanted PM who are candidates for upgrade and the results of the DANISH trial. 4,17 The issue of atrioventricular node ablation in patients with atrial fibrillation who receive an upgrade to CRT is another important point, and it should be stressed that atrioventricular node ablation is crucial for achieving the full benefit of CRT (by ensuring >95% ventricular pacing) even if no RCT validated the strategy of atrioventricular node ablation combined with CRT. 18 The data reported by Linde et al 5 prevalence of coronary artery disease, valvular heart disease, chronic kidney disease, anaemia, and atrial fibrillation.…”
mentioning
confidence: 99%